2021
DOI: 10.3390/ijms22020915
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gut Microbiota in an Ischemic Stroke

Abstract: The intestinal microbiome, the largest reservoir of microorganisms in the human body, plays an important role in neurological development and aging as well as in brain disorders such as an ischemic stroke. Increasing knowledge about mediators and triggered pathways has contributed to a better understanding of the interaction between the gut-brain axis and the brain-gut axis. Intestinal bacteria produce neuroactive compounds and can modulate neuronal function, which affects behavior after an ischemic stroke. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
96
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(98 citation statements)
references
References 91 publications
1
96
0
1
Order By: Relevance
“…This suggests that the gut microflora may control curcumin metabolism and bioavailability in the body. The gut microbiome changes throughout life [141] and progressive aging is associated with reduced microbial diversity in composition, quantity and quality, and the occurrence of cerebral ischemia [13,[142][143][144][145]. There are experimental indications that curcumin may modulate the composition of the gut microbes, including microbial diversity [86,[146][147][148][149].…”
Section: Curcumin Bioavailability and Gut Microbiomementioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the gut microflora may control curcumin metabolism and bioavailability in the body. The gut microbiome changes throughout life [141] and progressive aging is associated with reduced microbial diversity in composition, quantity and quality, and the occurrence of cerebral ischemia [13,[142][143][144][145]. There are experimental indications that curcumin may modulate the composition of the gut microbes, including microbial diversity [86,[146][147][148][149].…”
Section: Curcumin Bioavailability and Gut Microbiomementioning
confidence: 99%
“…It is now well known that post-ischemic brain neurodegeneration is caused by a set of genetic and proteomic changes that lead to neuronal death in an amyloid-and tau protein-dependent manner, with progressive inflammation resulting in brain atrophy with the development of full-blown Alzheimer's disease dementia [4,10,11]. Research indicates that after ischemia the brain can develop the typical neurodegeneration of Alzheimer's disease [3,4,[11][12][13][14][15][16][17][18][19][20][21][22]. First, post-ischemic brain damage causes selective neuronal death in the hippocampus typical of Alzheimer's disease with progressive brain atrophy [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…As it relates to therapeutic modalities targeted at manipulating the gastrointestinal microbiome, the administration of probiotics has arguably shown the most promise to date as an adjunct in symptomatic alleviation of several neurologic disease processes [ 90 , 91 , 92 ]. It is also the only relevant emerging intervention whose efficacy in neurologic injury patients has been evaluated in the clinical setting with human participants [ 93 , 94 ].…”
Section: Interventionsmentioning
confidence: 99%
“…19 A review has identified "two-way communication" between the gut and brain in ischemic stroke. 121 In summary, 5ARI-mediated changes in the neuroendocrine system, microbiome and epigenome could conceivably be downstream consequences of microvasculopathy or ischemia-reperfusion injury (Figure 11).…”
Section: Neuroendocrine Microbiotic and Epigenetic Changes Associated...mentioning
confidence: 99%